Music-related nostalgic experiences of young people living in migration - Khorsandi, Aida (2012)
Music is a powerful means for constructing identity – both formulating and remembering who one is (e.g., DeNora, 2000). A particular situation creating challenges for the sense of self is migration and living in a foreign environment. Therefore, this qualitative study focused on investigating music-related nostalgic experiences in young people living in migration. The aim of the study was to identify features characteristic to music-related nostalgia particularly in relation the experience of migration. Ten university students (aged between 24 – 40 years, 5 males, 5 females) took part in the study. The participants were all Iranian, currently living in migration (in Germany or Finland). Data was collected through spoken interviews (20-60min each) with an additional short questionnaire and a task to listen to self-selected music that participants found inductive of nostalgic experiences in them. The interviews focused on the participants’ current situation in the foreign country, their nostalgic experiences in general, and particularly in the role of music in their nostalgic experiences. The data was analysed qualitatively through the grounded theory approach. The results showed that the nostalgic memories of the participants focused on their home country; it’s specific places, characteristics (such as the humidity of north of Iran), and related experiences. The inclusion of music to nostalgic episodes appeared to intensify and stimulate the experience making it more vivid and detailed. The participants employed different strategic methods in how they used music-related nostalgia in their life: for counteracting loneliness, for evoking bittersweet emotions, for bringing continuity or new perspectives into one’s sense of self, finding meaning in life, and finding acceptance and sympathy for one’s feelings. Accordingly music seemed to play a triple role in nostalgic reverie; as a trigger for nostalgia, as a mean to recall and simulate the memory-related emotional state, and finally as a mood regulator tool. Furthermore, individual participants showed differences in their encounter style towards nostalgic experiences, preferring either avoidance or acceptance of the nostalgic mood. Preference for these styles was influenced by the personal experiences and mood (including depression) of the participants.